2013
DOI: 10.1097/pcc.0b013e3182745675
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Risk, Injury, Failure, Loss, End-Stage Renal Disease Score Identifies Acute Kidney Injury and Predicts Mortality in Critically Ill Children

Abstract: Objectives 1) To determine whether pRIFLE (Pediatric Risk, Injury, Failure, Loss, End Stage Renal Disease) criteria serves to characterize the pattern of Acute Kidney Injury (AKI) in critically ill pediatric patients; and 2) to identify if pRIFLE score will predict morbidity and mortality in our patient´s cohort. Design Prospective Cohort. Setting Multidisciplinary, tertiary care, 10- bed PICU. Patients 266 patients admitted to PICU from November 2009 to November 2010. Interventions None. Measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
109
3
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(135 citation statements)
references
References 19 publications
5
109
3
14
Order By: Relevance
“…In our analysis, the association of any AKI with increased mortality persisted when accounting for severity of illness. Patients with any evidence of AKI had 3.4 times increased odds of ICU mortality in our study, consistent with previous reports put forth by Alkandari [10,11,14,22]. In summary, our data shows that the KDIGO criteria describe clinically relevant AKI in a broad pediatric critical care population.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our analysis, the association of any AKI with increased mortality persisted when accounting for severity of illness. Patients with any evidence of AKI had 3.4 times increased odds of ICU mortality in our study, consistent with previous reports put forth by Alkandari [10,11,14,22]. In summary, our data shows that the KDIGO criteria describe clinically relevant AKI in a broad pediatric critical care population.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have shown that AKI is associated with increased mortality, length of mechanical ventilation, and length of stay (LOS) in a broad spectrum of pediatric patients [1,[4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…We also found that higher preoperative levels of CK-MB and h-FABP were associated with extended ICU and hospital LOS in addition to AKI, which is consistent with previous studies. [46][47][48][49] However, addition of AKI to these models did not attenuate the risk ratios, suggesting that the relationship between these biomarkers and extended LOS is mediated by factors other than AKI. These findings suggest that CK-MB and h-FABP may be superior to BNP in evaluating risk of postoperative AKI in children.…”
Section: Discussionmentioning
confidence: 99%
“…9 The justifi cation of frequent, costly SCr measurements is therefore diffi cult. Given the potential damage that is known from studies of AKI in adult and pediatric patients who did not examine nephrotoxin exposure specifi cally, 4,29,30 we believe more frequent measurement is indicated.…”
Section: Discussionmentioning
confidence: 99%